Evaluating the relationship between psychometric intelligence and cognitive functions in paediatric multiple sclerosis - Kapanci, Tugba (Mult Scler J Exp Transl Clin, 2019)
BACKGROUND: Processing speed is frequently reduced in patients suffering from multiple sclerosis (MS). Reduced processing speed can also lead to impaired working memory capacity (WMC) in adult MS patients. Less is known about the interplay of cognitive deficits in paediatric MS patients. OBJECTIVES: In the present study, we investigated whether processing speed and WMC are reduced in paediatric MS patients compared with healthy controls and whether reduced processing speed and WMC might explain potential differences in psychometric intelligence between MS patients and healthy controls. METHODS: Twenty-one paediatric MS patients and 21 healthy controls completed a reaction time (RT) task, a working memory task, and Cattell’s Culture Fair Test (CFT20-R). RESULTS: Patients with MS had slower RT and lower intelligence scores than healthy controls. We could find no significant differences for WMC. An analysis of covariance revealed that group differences in intelligence could be partially explained by processing speed differences. CONCLUSION: The results indicate that processing speed is a good marker for MS-related impaired efficiency and increased error-proneness of the central nervous system in higher-order cognition as required by Cattell’s CFT20-R.